2019
DOI: 10.1021/acs.iecr.9b01497
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Selective Toluene Sensor of Bimetallic Ni/Fe-MOFs Derived Porous NiFe2O4 Nanorods

Abstract: Here, we synthesized bimetallic Ni/Fe MOFs using 2-aminoterephthalic acid (NH2–BDC) as ligand by a facile hydrothermal route. After calcination, spindle-like Ni/Fe MOFs are transferred into porous NiFe2O4 nanorods. The resulting NiFe2O4 based sensor shows an excellent sensitivity (almost 60–500 ppm), good selectivity against various VOCs, and a good linearity in wide concentration and stability for toluene detection. Three major aspects of good catalytic activity, large surface area, and porous structures of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Permalloy has applications in areas, such as low frequency magnetic shielding and transformer cores, due to the successful combination of functional properties (high permeability, low coercivity, and small magnetic anisotropy) [ 4 , 5 , 6 , 7 , 8 ]. In addition, permalloy films are widely used as functional magnetic materials in magnetic field sensors (since they demonstrate the effects of giant and amorphous magnetoresistance) [ 9 , 10 , 11 ], magnetic recording devices [ 12 , 13 ], as spintronic material and as electromagnetic shields to protect functional electronics from permanent magnetic fields and electromagnetic radiations [ 14 , 15 ]. Ni-Fe alloys also show good corrosion resistance [ 16 ], good adhesion to various types of the substrates [ 7 , 14 , 15 ], and excellent mechanical characteristics (hardness in macro- and nanoscale, elastic modulus, wear and crack resistance, as well as resistance to plastic deformation) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Permalloy has applications in areas, such as low frequency magnetic shielding and transformer cores, due to the successful combination of functional properties (high permeability, low coercivity, and small magnetic anisotropy) [ 4 , 5 , 6 , 7 , 8 ]. In addition, permalloy films are widely used as functional magnetic materials in magnetic field sensors (since they demonstrate the effects of giant and amorphous magnetoresistance) [ 9 , 10 , 11 ], magnetic recording devices [ 12 , 13 ], as spintronic material and as electromagnetic shields to protect functional electronics from permanent magnetic fields and electromagnetic radiations [ 14 , 15 ]. Ni-Fe alloys also show good corrosion resistance [ 16 ], good adhesion to various types of the substrates [ 7 , 14 , 15 ], and excellent mechanical characteristics (hardness in macro- and nanoscale, elastic modulus, wear and crack resistance, as well as resistance to plastic deformation) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al prepared 1D α-Fe 2 O 3 /NiFe 2 O 4 heterojunction, which showed an improved response to acetone vapors using NiFe-bimetallic MOFs [39]. Previously, we prepared 1D porous NiFe 2 O 4 nanorods using 2-aminoterephthalic acid as the ligand, which showed excellent selectivity and sensitivity to toluene [40]. Nevertheless, as of now, tuning the NiFe 2 O 4 microstructures on a NiFe-bimetallic MOFs template base is still developing and in the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…[24] The stoichiometry and morphology of pristine MOF crystals can be transformed via calcination to corresponding metal oxide nanomaterials [25,26] which exhibit uniform shape, hierarchical porosity [27], and high surface areas. [28][29][30][31] MOF-derived complex metal oxides and their nanocomposites show excellent potential for electromagnetic wave absorption, [32] volatile organic compound sensing, [33,34] in catalysis [35,36] and energy storage applications. [25,37] For instance, MOF-derived NiFe2O4 nanorods, [33] AFe2O4 (A= Ni, Co, Zn) nanocubes, [38] NiFe2O4 polyhedra [34] and NiFe2O4…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] MOF-derived complex metal oxides and their nanocomposites show excellent potential for electromagnetic wave absorption, [32] volatile organic compound sensing, [33,34] in catalysis [35,36] and energy storage applications. [25,37] For instance, MOF-derived NiFe2O4 nanorods, [33] AFe2O4 (A= Ni, Co, Zn) nanocubes, [38] NiFe2O4 polyhedra [34] and NiFe2O4…”
Section: Introductionmentioning
confidence: 99%